Modelling the Development of the Integration Processes Direction in the Baking Industry - Tetyana Kublikova; Svetlana Stupak (CES Working Papers, 2013)
The paper presents the characteristics of the economic interaction between organizations and enterprises within the system of cluster type and the direction of their investment and innovation transformation through the implementation of the integration processes in the bakery industry.
Keywords: C35; C53; 330; cluster; correlation and regression analysis; system model Romania